HUBUNGAN USIA GESTASI DAN BERAT LAHIR NEONATUS DENGAN KEJADIAN IKTERUS NEONATORUM DI RSUD DR.M.HAULUSSY AMBON TAHUN 2018-2020 - Siti Aisyah Heringguhir; Merlin Margreth Maelissa; Sri Wahyuni Djoko (Fakultas Kedokteran Universitas Pattimura, 2022)
Neonatal jaundice is incident biological on baby that appears because production cell blood red tall and marked low bilirubin excretion with symptom skin colored yellow baby seen weak, urine colored dark until tanned. Reasons neonatal jaundice among other caused because maternal factors, perinatal factors neonate. Study aim for know connection age gestation dan heavy born neonate with jaundice neonatorum at RSUD dr. M. Haulussy Ambon in 2018-2020. Study this is research using design case control, data obtained is secondary data from record medical patients at RSUD dr. M. Haulussy Ambon obtained 154 samples . Data obtained analyzed use Statistical Package for the Social Science (SPSS) 26. Based on the results of the chi-square test, there was a significant relationship between gestational age (p=0.025) and the incidence of neonatal jaundice, as well as neonatal birth weight (p=<0.001). M. Haulussy Ambon 2018-2020.